Safety analysis of brachial artery sheath removal after heparin reversal with a half dose of protamine after percutaneous coronary intervention: a single-center experience - Wang, Huanhuan; Cui, Cheng; Liu, Dan; Liu, Hongmei; Tian, Tao; Liu, Minghao; Zhang, Bo; Zou, Tongqiang; Gao, Zhan; Gao, Lijian; Liu, Haibo (Frontiers in Cardiovascular Medicine, 2025)
AimTo evaluate the safety of brachial artery (BA) sheath removal after heparin neutralization with a half dose of protamine immediately after percutaneous coronary intervention (PCI).MethodsThe clinical data of 209 consecutive patients who underwent PCI through the BA at Fu Wai Hospital between September 2019 and June 2024 were retrospectively collected. In group I, the brachial sheath was removed 4 h after the PCI procedure. In group II, circulating heparin was neutralized with a half dose of protamine sulfate, and the brachial sheath was removed immediately after the procedure.ResultsThere were no cases of acute stent thrombosis, nonfatal myocardial infarction or in-hospital mortality in either group. In group II, there were two cases of pseudoaneurysm, one of which was transfer to surgery and the other was manually compressed. No severe puncture site-related bleeding occurred. The levels of hemoglobin were similar between the two groups before and after the PCI procedure (p > 0.05).ConclusionsThe BA sheath can be safely removed immediately after PCI by neutralizing heparin with a half dose of protamine. But we still need to be vigilant about the occurrence of pseudoaneurysms.